Interplay between recombination, cell division and chromosome structure during chromosome dimer resolution in Escherichia coli. - Pérals, K; Capiaux, H; Vincourt, J; Louarn, J; Sherratt, D; Cornet, F (2001)
Chromosome dimers form in bacteria by recombination between circular chromosomes. Resolution of dimers is a highly integrated process involving recombination between dif sites catalysed by the XerCD recombinase, cell division and the integrity of the division septum-associated FtsK protein and the presence of dif inside a restricted region of the chromosome terminus, the dif activity zone (DAZ). We analyse here how these phenomena collaborate. We show that (i) both inter- and intrachromosomal recombination between dif sites are activated by their presence inside the DAZ; (ii) the DAZ-specific activation only occurs in conditions supporting the formation of chromosome dimers; (iii) overexpression of FtsK leads to a general increase in dif recombination irrespective of dif location; (iv) overexpression of FtsK does not improve the ability of dif sites inserted outside the DAZ to resolve chromosome dimers. Our results suggest that the formation of an active XerCD-FtsK-dif complex is restricted to when a dimer is present, the features of chromosome organization that determine the DAZ playing a central role in this control.